A Correlational Study on The Relationship Between Students’ English Vocabulary Proficiency and Their Listening Habits in English Music - Muhammad Baiqun Isbahi (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2023)
This study looked at the association between students’ listening habits to English music and their vocabulary knowledge. This was a quantitative study that used the correlation method. The population consisted of all second-semester students from a college in Mojokerto, which consists of two classes totaling 40 students. The sample consisted of 17 students chosen at random using the incidental sampling technique. The questionnaire and vocabulary test were used to collect data in this study. The questionnaire was used to collect information on students’ listening habits to English music, while the assessments were used to obtain information about students’ vocabulary competence. The researcher utilized Kendall’s tau b in the IBM SPSS Statistics 25 program for Windows to analyze the data. The study’s findings revealed a substantial association between students’ listening habits to English music and their vocabulary competence. Furthermore, there is a positive link with a moderate level of significance. As a result, pupils’ habit of listening to English music contributes to their vocabulary mastery.